2021
DOI: 10.3390/ijerph18094927
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Cardiovascular Risk Factors Associated with Drug Use in Truck Drivers in the State of São Paulo, Brazil: A Cross-Sectional Study

Abstract: The aim of the study is to analyze the association between risk factors for the health of truck drivers and previous use of illicit drugs. A cross-sectional study examined the data from 2071 truck drivers between 2010 and 2016. Demographic variables, risk factors for cardiovascular disease (CVD) and the use of illicit drugs were analyzed. The stepwise logistic regression model was used for the adjusted analysis. The dependent variable was the previous use of illicit drugs, and independent variables were those … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…There are a lot of articles about alcohol, tobacco and illicit drugs consumption in groups of truck drivers through questionnaires across the country (Oliveira et al, 2013;Berti et al, 2013;Takitane et al, 2013;Domingos et al, 2014, Oliveira et al, 2016, Pereira et al, 2021, Scherer et al, 2021. However, this one is the first study that estimated the prevalence of these drugs through a questionnaire validated by the World Health Organization (WHO), as well as the initiative to list the intervention procedures and/or treatment to be used in participants who do consume abuse of licit and illicit substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a lot of articles about alcohol, tobacco and illicit drugs consumption in groups of truck drivers through questionnaires across the country (Oliveira et al, 2013;Berti et al, 2013;Takitane et al, 2013;Domingos et al, 2014, Oliveira et al, 2016, Pereira et al, 2021, Scherer et al, 2021. However, this one is the first study that estimated the prevalence of these drugs through a questionnaire validated by the World Health Organization (WHO), as well as the initiative to list the intervention procedures and/or treatment to be used in participants who do consume abuse of licit and illicit substances.…”
Section: Discussionmentioning
confidence: 99%
“…Many articles have been published about the use and abuse of drugs by truck drivers in Brazil (Silva et al, 2003;Leyton et al, 2011;Oliveira et al, 2013;Yonamine et al, 2013, Pereira et al, 2021. They showed that driving under the influence of alcohol or drugs, high speed and young age, are major risk factors related to the number of traffic accidents on the roads.…”
Section: Introductionmentioning
confidence: 99%
“…In Latin America, several studies were found involving this population concerning various risk factors. Pereira et al [ 12 ] investigated the association between risk factors for the health of truck drivers and previous use of illicit drugs, in Brazil. Yonamine et al [ 13 ] investigated alcohol consumption and the use of stimulant drugs in Brazilian truck drivers.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, few studies have been conducted on truck drivers' tobacco use 3,4,9 and, to our knowledge, none have investigated the use of this substance and nicotine dependence as dependent variables and sought to identify their associated factors. Such data are key for planning multifaceted actions and public policies to control the use of this substance in this population, such as permanent education for health care teams, especially primary health care for screening and smoking cessation interventions in this population; expansion of the treatment of nicotine dependence in the Unified Health System (SUS), including non-drug and drug aspects; specific campaigns for health education aimed at truck drivers, strengthening worker health promotion strategies in transport companies; periodic adjustments to the main taxes on cigarettes and the prices of these products at retail; promotion of tobacco-free environments, including those roadside establishments; and strengthening of tobacco control policies in Brazil, like the National Anti-Smoking Program and cross-cutting policies such as the National Health Promotion Policy and the National Primary Care Policy, among others.…”
Section: Introductionmentioning
confidence: 99%